PENGARUH TEKNIK BIBLIOTERAPI TERHADAP KEPERCAYAAN DIRI SISWA DI SMP NEGERI 6 BUKITTINGGI - Novia Anggelica Pane; Fadhilla Yusri (CV. ADIBA AISHA AMIRA, 2025)
The reason behind the author's interest in writing this thesis is because there are still students who have problems with self-confidence. For example, when students are given the opportunity to tell stories, many students remain silent, there are still students who do not dare to express their opinions, there are still students who break out in cold sweat, there are still students who don't dare to express their opinions. who is shy when communicating. This research aims to determine the effect of bibliotherapy techniques on students' self-confidence at SMP Negeri 6 Bukittinggi. This type of research is Pre-Experimental Design using the One Group Pretest-Posttest model. The population in this study was class VII. The sample for this research consisted of 8 people who were taken using a purposive sampling technique, which means the technique of determining the sample using certain considerations. Data was collected using a scale for developing student self-confidence. The data analysis technique used is the Wilcoxon test. The research results show that the influence of students' self-confidence before being given group counseling services using bibliotherapy techniques is in the medium category with a mean of 124.88. and the effect after being provided with group counseling services using bibliotherapy techniques was in the high category with an increasing score with a mean of 140.851. This statement is supported by the asymp sig (2-tailed) results which obtained a value of 0.008, which means it is smaller than the α value of 0.05. So it can be said that Ha was accepted and Ho was rejected, meaning that group counseling using bibliotherapy techniques had an effect on increasing the self- confidence of students at SMP Negeri 6 Bukittinggi.